Intergovernmental Relations and Fiscal Discipline : Between Commons and Soft Budget Constraints - Pisauro, Guiseppe (IMF Working Papers; Working Paper, 2001)
Fiscal decentralization is likely to entail a bias in the budget process toward higher public expenses and deficits. The paper reviews lessons drawn from the theoretical literature and international experience on the design of intergovernmental relations. The institutional setup should address the dual problem of "common tax resources" and "soft" budget constraints, where policies devised to correct one problem may exacerbate the other. An approach based on full tax autonomy of lower-tier governments and reliance on market discipline, not supplemented by self-imposed constitutional limits, is not advisable. More effective seems to be a cooperative approach with some preeminence granted to the central government.